Early German Sound Sourcing with Songs in the Trilogy of the Mackeben-Jugo-Engel Ensemble - Wager, Gregg (Journal of Film Music, 2017)
Once German filmmakers had accepted the advent of talking motion pictures as an inevitable and important technological and aesthetic development in cinema, they anticipated a drastic shift in their foreign markets based on a language barrier that was more difficult to overcome than with silent films. While Germans still closely studied practices in the new synchronized sound in America’s Hollywood, their own experiments with how to use music in the enhanced medium still raised similar issues, but stylistically took cinema in slightly different directions based on the origins and development of the music itself. Composer Theo Mackeben, actress Jenny Jugo, and director Erich Engel collaborated on three comedies together during this era that emphasized original songs, culminating in a storytelling style that utilized both the fantasy of a recurring melody throughout the story featuring various kinds of source music, and the realism of having a character introduce the song without suspending the story as musicals often do. When the Nazi influence took hold, phasing out jazz music and attempting to deliberately introduce German folk elements into the movies, the intrusive new propaganda rules became obstacles to steer creative energies and innovation around.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTU1OC9qZm0uMjcwOTY